Pengaruh Green Human Resource Management terhadap Kinerja Karyawan - Muhammad Fikri Imaduddin; Sri Suwarsi (UNISBA Press, 2023)
Abstract. The production and distribution process in the business flow causes nature to be damaged and its balance is disturbed. All kinds of aspects have contributed to the destruction of nature that is happening now. In the development of science, various kinds of breakthroughs have been made to at least reduce the environmental damage that occurs, one of which is through the implementation of environmentally friendly human resource management. In previous studies that have been conducted, it has been stated that the implementation of environmentally friendly human resource management has a positive effect on performance. This study aims to 1) To find out the implementation of Green Human Resource Management at Bank Bjb. 2) To find out the performance of employees at Bank Bjb. 3) To determine the effect of implementing Green Human Resource Management on employee performance at Bank Bjb. The sampling technique is Nonprobability Sampling, namely by using a saturated sample where the entire population in the research object is used as a sample. This study used descriptive and verification methods with a total of 48 employees using data collection techniques from field research and library research. The results of this study conclude that: 1) Green Human Resource Management in the Human Capital Division, Bank Bjb Head Office, Bandung City is in the Good category. 2) Implementation of Employee Performance is in the Good category. 3) Green Human Resource Management has a direct influence on the performance of employees of the Human Capital Division at Bank Bjb Head Office, Bandung City. It can be concluded that there is an influence between Green Human Resource Management on the performance of employees of the Human Capital Division at Bank Bjb Head Office, Bandung City. Abstrak. Proses produksi dan distibusi pada alur bisnis menyebabkan alam saat ini semakin rusak dan terganggu keseimbangannya. Segala macam aspek telah berkontribusi dalam kerusakan alam yang terjadi sekarang. Dalam pengembangan ilmu pengetahuan berbagai macam terobosan telah dilakukan untuk setidaknya mengurangi kerusakan lingkungan yang terjadi, salah satunya melalui implementasi manajemen sumber daya manusia ramah lingkungan. Dalam penilitian-penelitian sebelumnya yang telah dilakukan menyebutkan bahwasanya implementasi manajemen sumber daya manusia ramah lingkungan berpengaruh positif terhadap kinerja. Penelitian ini bertujuan untuk 1) Untuk mengetahui penerapan Green Human Resource Management di Bank Bjb. 2) Untuk mengetahui kinerja karyawan di Bank Bjb. 3) Untuk mengetahui pengaruh penerapan Green Human Resource Management terhadap kinerja karyawan di Bank Bjb. Teknik penarikkan sampel adalah Nonprobability Sampling yaitu dengan menggunakan sampel jenuh dimana seluruh populasi di objek penelitian dijadikan sampel. Penelitian ini menggunakan metode deskriptif dan metode verifikatif dengan jumlah responden sebanyak 48 karyawan menggunakan teknik pengumpulan data penelitian lapangan dan penelitian kepustakaan. Hasil penelitian ini menyimpulkan bahwa: 1) Green Human Resource Management di Divisi Human Capital Kantor Pusat Bank Bjb Kota Bandung termasuk kategori Baik. 2) Penerapan Kinerja Karyawan termasuk kategori Baik. 3) Green Human Resource Management memiliki pengaruh langsung terhadap kinerja karyawan Divisi Human Capital Kantor Pusat Bank Bjb Kota Bandung. Dapat disimpulkan bahwa terdapat pengaruh antara Green Human Resource Management terhadap kinerja karyawan Divisi Human Capital Kantor Pusat Bank Bjb Kota Bandung.